Cooperating to avoid catastrophe. (July 2018) - Dannenberg, Astrid; Barrett, Scott
Knowledge that humans could trigger a regime shift in a vital natural system may help in identifying a goal for collective action, but it is unlikely to spur the degree of cooperation needed to avert a catastrophe. Substantial behaviour change can be achieved by manipulating the institutions that govern human action on the commons.